The PPP - Perineal Body Preserving PSARP (Posterior Sagittal Anorectoplasty) for Anorectal Malformation with Rectovestibular Fistula in Females—Report of Early Outcomes - Xu, Thomas O.; Ryan, Julia Ann; Feng, Christina; Badillo, Andrea; Sandler, Anthony; Levitt, Marc A. (European Journal of Pediatric Surgery, 2024)
Introduction The perineal body preserving posterior sagittal anorectoplasty (PSARP) (PPP) is a novel modification of the original PSARP for female patients with rectovestibular fistulas designed to eliminate the risk of perineal body dehiscence. This study aims to examine the outcomes following PPP.Methods A retrospective, single-institution study was performed examining female patients with rectovestibular fistula who underwent PPP between January /2020 and December 2023. Exposure was done through the intended anoplasty only. Perineal body or posterior sagittal incision was not utilized. No routine postoperative dilations were performed. The postoperative outcomes, day of discharge, time to first feeding, and early stooling patterns were assessed.Results A total of 15 patients underwent a PPP at a median age of 6 months (range 2 days to 19 months) with median follow-up of 11 months (range 1–36). Three (20%) patients underwent repair within the first 3 months of life. Five (33%) had diverting ostomies prior to referral to our team. There was no incidence of dehiscence or rectal prolapse. Two (13%) patients developed an anal stricture which required revision. Fourteen (93%) patients resumed normal feeds on postoperative day 1. Eleven (73%) were discharged on postoperative day 1. All patients were stooling spontaneously at their most recent clinical encounter with 11 (73%) utilizing laxatives.Conclusions PPP eliminates the risk of perineal body dehiscence and has a quick return to regular diet and home. There is a 13% stricture rate which could relate to a difference in the distal rectal mobilization compared with the traditional PSARP.
Keywords: anorectal malformation; rectovestibular fistula; posterior sagittal anorectoplasty; operative technique; perineal body dehiscence